Small copepods matter: Population dynamics of Microsetella norvegica in a high-latitude coastal ecosystem - Svensen, Camilla; Antonsen, Maria Terese; Reigstad, Marit (Journal of Plankton Research, 2018)
This is a pre-copyedited, author-produced version of an article accepted for publication in Journal of Plankton Research following peer review. The version of record Svensen, C., Antonsen, M.T. & Reigstad, M. (2018). Small copepods matter: Population dynamics of Microsetella norvegica in a high-latitude coastal ecosystem. Journal of Plankton Research , 40(4), 446-457 is available online at: https://doi.org/10.1093/plankt/fby019 . We investigated the population dynamics of a small and little-studied harpacticoid copepod, Microsetella norvegica , in a sub-Arctic Norwegian fjord (Balsfjord 69°N). We sampled with a 90 μm mesh WP-2 net and a 20 L Go-Flo bottle and found that the WP-2 under-sampled all juvenile stages. The abundance and biomass were high, peaking in June with 9349 × 10- 3 ind. m −2 and 1678 mg C m −2 . Microsetella were most abundant in the surface, but females and males demonstrated a distinct migration to below 50 m from October to March. Consistently, individual female body carbon content was highest in October (0.39 μg C ind −1 ) and lowest in March (0.18 μg C ind −1 ). Males were present throughout the year, and females with eggs were found from April to September. The average clutch size was 11 ± 2 eggs female −1 , and our study supports the observation that females can release their egg sac before the eggs have hatched, possibly to produce a new one. With its high abundance and biomass, a flexible reproductive strategy and specialized feeding preferences, M. norvegica is likely a key species in high-latitude coastal ecosystems.